Increased Sodium Concentration in Substantia Nigra in Early Parkinson's Disease: A Preliminary Study With Ultra-High Field (7T) MRI - Grimaldi, Stephan; El Mendili, Mohamed Mounir; Zaaraoui, Wafaa; Ranjeva, Jean-Philippe; Azulay, Jean-Philippe; Eusebio, Alexandre; Guye, Maxime (Frontiers in Neurology, 2021)
Pathophysiology of idiopathic Parkinson's disease (iPD) is complex and still misunderstood. At a time when treatments with disease-modifying potential are being developed, identification of early markers of neurodegeneration is essential. Intracerebral sodium accumulation could be one of them. Indeed, it may be in relation to the mitochondrial dysfunction that early exists in iPD. For the first time, we used brain sodium (23Na) MRI to explore sodium concentration changes that have already been reported to be related to neurodegeneration in other diseases. We prospectively included 10 iPD patients (mean age 52.2 ± 5.9 years-old) with motor symptoms that started <36 months before inclusion and 12 healthy subjects (mean age 53 ± 6.4 years-old). Patients were scanned in OFF medication state by using proton (1H) and 23Na MRI at 7T. We then extracted quantitative Total Sodium Concentration (TSC) from five regions of interest known to be early impaired in iPD [substantia nigra (SN), putamen, caudate nucleus, pallidum, thalamus] and in one region supposed to be relatively spared in the first stages of the disease [cortical gray matter (neocortex)]. Potential atrophy in these structures was also investigated with 1H MRI. Relative to healthy subjects, iPD patients showed higher TSC in the SN (43.73 ± 4.64 vs. 37.72 ± 5.62, p = 0.006 after Bonferroni correction). A trend of increase in sodium concentrations was found within the pallidum (45.80 ± 4.19 vs. 41.07 ± 4.94, p = 0.017), putamen (48.65 ± 4.58 vs. 43.66 ± 5.04, p = 0.041) and the cortical gray matter (56.34 ± 3.92 vs. 50.81 ± 5.50, p = 0.021). No significant brain atrophy was found in patients compared to controls. Thus, alteration of sodium homeostasis in the SN in the absence of atrophy could be considered as a potential early marker of cellular dysfunction in iPD.